2020
DOI: 10.3390/jcm9113624
|View full text |Cite
|
Sign up to set email alerts
|

First Wave of COVID-19 in French Patients with Cystic Fibrosis

Abstract: Viral infections are known to lead to serious respiratory complications in cystic fibrosis (CF) patients. Hypothesizing that CF patients were a population at high risk for severe respiratory complications from SARS-CoV-2 infection, we conducted a national study to describe the clinical expression of COVID-19 in French CF patients. This prospective observational study involves all 47 French CF centers caring for approximately 7500 CF patients. Between March 1st and June 30th 2020, 31 patients were diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 45 publications
6
76
3
1
Order By: Relevance
“…In the ECFSPR geographic area, the overall incidence of SARS-CoV-2 in pwCF was not significantly different to the incidence of that of the corresponding general population (2.70 versus 3.10/1000). SARS-CoV-2 was lower in pwCF versus the general population in studies from a global group (0.7/1000 versus 1.5/1000 up to mid-April 2020) [7] , Spain (3.2/1000 versus 4.9/1000 up to 16 May 20) [19] , France (4.1/1000 pwCF up to 30 June 20) [5] , Italy (15.8/1000 versus 29.1/1000 up to November 2020) [20] and Verona, Italy (1.9/1000 versus 4/1000 up to 23 July 20) [21] .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the ECFSPR geographic area, the overall incidence of SARS-CoV-2 in pwCF was not significantly different to the incidence of that of the corresponding general population (2.70 versus 3.10/1000). SARS-CoV-2 was lower in pwCF versus the general population in studies from a global group (0.7/1000 versus 1.5/1000 up to mid-April 2020) [7] , Spain (3.2/1000 versus 4.9/1000 up to 16 May 20) [19] , France (4.1/1000 pwCF up to 30 June 20) [5] , Italy (15.8/1000 versus 29.1/1000 up to November 2020) [20] and Verona, Italy (1.9/1000 versus 4/1000 up to 23 July 20) [21] .…”
Section: Discussionmentioning
confidence: 93%
“…Upon SARS-CoV-2 infection, lung-transplanted pwCF were more frequently symptomatic, were admitted to hospital 1.7-fold more frequently and required intensive care 8-fold more frequently than pwCF without lung transplant. Previous studies also found that solid organ transplant recipients require more treatment and medical care upon SARS-CoV-2 infection, whether transplant was for CF [ 5 , 7 ] or other reasons [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 31, 61% had been hospitalized and 13% (4/31) were in the ICU. [12]. For PCD, we found that most people who tested positive for SARS-COV-2 had mild symptoms, only 1 (8%) was hospitalised and none was in the ICU.…”
mentioning
confidence: 98%
“…Results overall are comparable to what has been found for cystic fibrosis (CF). A French study of 7500 CF patients from 47 clinics found that 31 had tested positive for SARS-CoV-2 by June 2020, 0.4% of the study population [12]. Among the 31, 61% had been hospitalized and 13% (4/31) were in the ICU.…”
mentioning
confidence: 99%